2013
DOI: 10.1016/j.ophtha.2013.07.050
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Socioeconomic Deprivation on Corneal Graft Survival in the United Kingdom

Abstract: Patients classified as hard-pressed had an increased risk of graft failure within 5 years compared with the least deprived patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 19 publications
0
12
0
1
Order By: Relevance
“…IMD data have successfully been used to highlight social deprivation as an independent risk factor for many systemic diseases 5. In terms of eye disease, the IMD has been used to evaluate the impact of deprivation on low vision7 and a significant factor in the prevalence or presentation of a number of specific eye conditions, including severe neovascular age-related macular degeneration,8 glaucoma9 10 and cataract 11…”
Section: Introductionmentioning
confidence: 99%
“…IMD data have successfully been used to highlight social deprivation as an independent risk factor for many systemic diseases 5. In terms of eye disease, the IMD has been used to evaluate the impact of deprivation on low vision7 and a significant factor in the prevalence or presentation of a number of specific eye conditions, including severe neovascular age-related macular degeneration,8 glaucoma9 10 and cataract 11…”
Section: Introductionmentioning
confidence: 99%
“…In their study population in Hyderabad, India, Dandona et al found that patients of lower socioeconomic status had a 1.28 times higher risk of graft failure compared with patients of higher socioeconomic status [ 10 ]. In a nationwide study using the United Kingdom Transplant Registry, Chua et al found that the risk of graft failure within 5 years post operation of patients classified as hard-pressed was 1.3 times higher than that of patients classified as wealthy achievers [ 20 ]. In this study, we found that compared to patients who completed college or university, the risk of graft failure was 4.7 times higher among patients with less education.…”
Section: Discussionmentioning
confidence: 99%
“…A considerable number of patients are not satisfied with the results of corneal transplantation (14) as it has reduced their social emotions and, as a result, their quality of life (17). In addition, the results have demonstrated that improved vision has a direct association with limitations caused by mood disorders and social performance in patients, so that severe socio-economic restrictions have been shown to increase the risk of corneal transplant rejection (18). Examining and understanding the implications of life with a grafted cornea leads to deep insight in this area that can be added to the body of knowledge of nursing, and help nurses in providing services and optimal care of patients.…”
Section: Introductionmentioning
confidence: 99%